Distributional national accounts (DINA) for Austria, 2004-2016 - Stefan Jestl; Emanuel List (The Vienna Institute for International Economic Studies (wiiw), 2020)
This paper constructs distributional national accounts for Austria for the period 2004-2016. We enrich survey data with tabulated tax data and make it fully consistent with national accounts data. The comprehensive dataset allows us to analyse the distribution of macroeconomic growth across the income distribution and to explore the evolution of income inequality in pre-tax income over time. Our results suggest that the distribution of growth has changed over time, which had considerable repercussions on inequality. Inequality started to decline at the very beginning of the economic and financial crisis in 2007, however it has increased again after 2012. We further provide novel insights into the evolution of capital income for top income groups and explore redistribution mechanisms that operated in Austria. Government spending was found to play a key role for redistributive effects across the income distribution. In particular, the transfer system redistributes pre-tax income to a large extent.
Keywords: C55; D31; E01; 330; Distributional national accounts; Austria; survey data; tax data; income inequality